Why Does Rapid Naming Predict Chinese Word Reading?. Issue 1 (2nd January 2017) - Shum, Kathy Kar-man; Au, Terry Kit-fong
ABSTRACT: Rapid automatized naming (RAN) robustly predicts early reading abilities across languages, but its underlying mechanism remains unclear. This study found that RAN associated significantly with processing speed but not with phonological awareness or orthographic knowledge in 89 Hong Kong Chinese second-graders. RAN overlaps more with processing speed (18% of individual variation) in predicting word reading fluency, than with phonological (4%) or orthographic awareness (3%), suggesting that processing speed contributed more strongly to the RAN-reading fluency relation in Chinese. Nonetheless, RAN remained significant in predicting Chinese word-level reading fluency when all other cognitive tasks were taken into account, suggesting that no single construct can fully explain RAN's relation to reading, but that multiple components influence this relation. Moreover, when reading abilities in second language English were considered, the association between RAN and word reading fluency was marginally stronger in Chinese than in English. Implications for mechanisms underlying the RAN-reading relation are discussed.